ZIF-8 modified fiber filtering membrane and preparation method thereof
Through multi-needle electrospinning technology combined with stereostructural composite polylactic fiber and ZIF-8 nanocrystals, the fiber filter membrane has poor high temperature resistance and poor sterilization effect, and has achieved efficient interception of ultra-fine particles and improved antibacterial performance. .
Patent Information
- Application Number
- CN202411647947.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2024-12-31
AI Technical Summary
The existing fiber filter membranes have poor high temperature resistance and poor sterilization effect. Traditional polylactic acid fibers have slow crystallization rate and low crystallinity during processing, resulting in poor heat resistance. Moreover, ZIF-8 cannot be effectively embedded in polymers. Its characteristics.
Using multi-needle electrospinning technology, ZIF-8 dispersion, the first spinning solution and the second spinning solution are electrospinned to form a ZIF-8 modified fiber filter membrane, and stereocomplex polylactic fibers and beads are used. The structure is combined and closely embedded in ZIF-8 nanocrystals improves the surface potential and dielectric constant of the fibers and enhances antibacterial properties.
High surface potential, high dielectric constant, high specific surface area, high efficiency antibacterial, ultra-low air resistance and high heat resistance are achieved, significantly improving the removal efficiency and antibacterial effect of ultra-fine particles.
Smart Images

Figure CN119215677A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber membrane materials for air filtration, and in particular to a ZIF-8 modified fiber filtration membrane and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of industrialization and urbanization, air pollution caused by particulate matter (PM) has become one of the most important environmental issues and has received increasing attention. In particular, PMs with an aerodynamic diameter of less than 2.5 μm are prone to carry toxic and harmful substances (such as heavy metals, microorganisms, etc.), which can enter the bronchi and lungs of the human body almost unimpeded, thereby causing respiratory infections, lung cancer, and cardiovascular diseases. Therefore, in order to cut off the spread of viruses and protect human health, it is urgent to develop high-efficiency air filtration materials.
[0003] Filtration is one of the most effective measures to reduce air pollution. However, most traditional air filter materials are composed of micron-sized fibers, which have poor surface electrostatic adsorption effects and cannot effectively intercept fine or even ultrafine PMs. In recent years, with the development of fiber manufacturing technology, electrospinning technology has gradually entered the public eye. The nanofiber membrane produced by electrospinning technology has the advantages of porous structure, controllable diameter, high specific surface area, good internal connectivity, uniform morphology, and excellent mechanical properties. Electrospinning technology can directly and continuously prepare micro- and nanofibers, showing good application prospects in the field of air filtration materials. However, most chemically synthesized polymers face a common problem: non-renewability, non-reusability, and non-biodegradability, which will lead to secondary environmental problems. Therefore, the development of natural or biodegradable polymer filtration membranes is of great scientific and technological significance for reducing environmental pollution and building a sustainable society.
[0004] Polylactic acid (PLA) is a non-petroleum-based polymer material with excellent renewability, biodegradability, biocompatibility and mechanical properties, and is one of the most widely used biodegradable polymers. However, due to the strong rigidity of the PLA molecular chain and the steric hindrance of the side chain methyl group, the mobility of the PLA chain segment is limited, and the PLA crystallization rate is slow and the crystallinity is low during the processing, resulting in poor heat resistance of PLA products.
[0005] At present, most polylactic acid products do not have high temperature resistance. This is because the crystallization rate of PLA is slow and the crystallinity is low during the processing, resulting in poor heat resistance of PLA products. At the same time, most reports are that ZIF-8 materials are doped in other polymer solutions for electrospinning. This method can only control the loading amount of ZIF-8, but ZIF-8 is embedded in the polymer and cannot effectively exert the characteristics of ZIF-8 materials. In addition, the filtration efficiency of polylactic acid fiber filter membrane is usually proportional to the pressure drop. This is mainly because electrospun fibers are generally round and smooth in shape, with a small fiber diameter, which is conducive to high filtration efficiency of PM. However, the above characteristics, in turn, will cause the nanofibers to be densely packed, resulting in a high packing density, which increases the filtration resistance and energy consumption. Summary of the invention
[0006] The main purpose of the present invention is to provide a ZIF-8 modified fiber filtration membrane and a preparation method thereof, so as to solve the problems of poor high temperature resistance and poor sterilization effect of the fiber filtration membrane in the prior art.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a ZIF-8 modified fiber filtration membrane is provided, which comprises: subjecting a ZIF-8 dispersion, a first spinning solution and a second spinning solution to multi-needle electrospinning to obtain a ZIF-8 modified fiber filtration membrane; wherein the mass ratios of poly-L-lactic acid and poly-D-lactic acid in the first spinning solution and the second spinning solution are independently 1:1 to 50:1, and the sum of the concentrations of poly-L-lactic acid and poly-D-lactic acid in the first spinning solution is 80 to 100 g / L; and the sum of the concentrations of poly-L-lactic acid and poly-D-lactic acid in the second spinning solution is 60 to 80 g / L.
[0008] Further, the ZIF-8 dispersion includes ZIF-8 crystals, a dispersant and a first solvent;
[0009] The ZIF-8 crystal has a rhombic dodecahedral structure. Preferably, the particle size of the ZIF-8 crystal is 300 to 500 nm, and the pore size is 0.2 to 0.34 nm;
[0010] The dispersant is at least one of polyvinyl pyrrolidone, hexadecyl trimethyl ammonium bromide solution, and sodium hexadecyl benzene sulfonate;
[0011] The first solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, dichloromethane, chloroform, tetrahydrofuran, chloroform and ethanol;
[0012] Preferably, the mass ratio of ZIF-8 crystals to the first solvent is 1:1000 to 1:20, and the mass ratio of ZIF-8 crystals to the dispersant is 5:1 to 20:1.
[0013] Furthermore, the preparation method of ZIF-8 crystals includes: mixing a 2-methylimidazole aqueous solution, a template agent and a zinc salt solution, reacting under microwave conditions, and obtaining ZIF-8 nanocrystals after extraction and drying;
[0014] The template agent is at least one of ethanolamine, diethylamine, l-histidine, polyethylene glycol, sodium dodecyl sulfate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide, and the mass ratio of 2-methylimidazole to the template agent is 50:1 to 600:1;
[0015] The zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate, the concentration of the zinc salt solution is 0.02 to 5 mol / L, and the molar ratio of 2-methylimidazole to the zinc salt is 7:1 to 10:1;
[0016] Preferably, the reaction temperature is 80-200°C and the reaction time is 5-120 min;
[0017] Preferably, the output power of the microwave reaction device providing the microwave condition is 200-1500W.
[0018] Further, the solvents of the first spinning solution and the second spinning solution are independently selected from any one or more of dimethylformamide, ethyl acetate, acetone, dichloromethane, chloroform and ethanol.
[0019] Furthermore, in the multi-needle electrospinning, the inner diameter of the spinning metal needle used in the first spinning solution is 0.60 to 0.86 mm, the positive voltage used is 10 to 20 kV, and the negative voltage is 1 to 5 kV;
[0020] The consumption rate of the first spinning solution is 2-3 mL / h, the receiving distance is 10-30 cm, and the roller rotation speed is 500-1500 rpm.
[0021] Furthermore, in the multi-needle electrospinning, the inner diameter of the spinning metal needle used in the second spinning solution is 0.33 to 0.50 mm, the positive voltage used is 15 to 30 kV, and the negative voltage is 1 to 15 kV;
[0022] The consumption rate of the second spinning solution is 0.5-2 mL / h, the receiving distance is 10-30 cm, and the roller rotation speed is 500-1500 rpm.
[0023] Furthermore, in multi-needle electrospinning, the inner diameter of the spinning metal needle used for the ZIF-8 dispersion was 0.33 to 0.86 mm, the positive voltage used was 5 to 30 kV, and the negative voltage was 1 to 15 kV;
[0024] The consumption rate of ZIF-8 dispersion is 0.1-2 mL / h, the receiving distance is 5-20 cm, and the roller speed is 100-1000 rpm.
[0025] Further, the environment temperature of the multi-needle electrospinning is 20-30°C and the relative humidity is 25-45%;
[0026] The diameter of the fiber obtained by the first spinning solution is 1 to 15 μm;
[0027] The diameter of the fiber obtained by the second spinning solution is 30 to 300 nm.
[0028] Furthermore, the ZIF-8 modified fiber filtration membrane includes a beaded structure, the beaded structure has an elongated spindle shape, an average width of 500 to 1000 nm, and an average length of 600 to 1500 nm;
[0029] The thickness of the ZIF-8 modified fiber filtration membrane is 80 to 300 μm;
[0030] The surface potential of the ZIF-8 modified fiber filtration membrane is 7 to 15.5 kV;
[0031] The dielectric constant of the ZIF-8 modified fiber filtration membrane is 5 to 13 F / m;
[0032] The specific surface area of the ZIF-8 modified fiber filtration membrane is 330.5-550.5 m 2 / g;
[0033] Under light conditions, the antibacterial rate of the ZIF-8 modified fiber filtration membrane against Escherichia coli was greater than or equal to 97.6%, and the antibacterial rate against Staphylococcus aureus was greater than or equal to 99.5%.
[0034] At a gas flow rate of 10 to 85 L / min, the air resistance of the ZIF-8 modified fiber filtration membrane was low, ≤100 Pa;
[0035] At 100 °C, the ZIF-8 modified fiber filtration membrane has a significant effect on PM 0.3 The removal efficiency is greater than or equal to 90.5%; for PM 2.5 The removal efficiency is greater than or equal to 99.5%.
[0036] In order to achieve the above object, according to one aspect of the present invention, a ZIF-8 modified fiber filtration membrane is provided, which is prepared by any of the above methods for preparing a ZIF-8 modified fiber filtration membrane.
[0037] By applying the technical solution of the present invention, a blended solution of poly (dextral lactic acid) and poly (lactic acid) is electrospun to form a stereocomposite polylactic acid fiber, wherein the stereocomposite crystals in the stereocomposite polylactic acid fiber can effectively increase the crystallinity of PLA and improve the heat resistance of PLA products. The above preparation method constructs a beaded structure along the axis of the nanofiber to optimize the packing density of the nanofiber and adjust the distance between the nanofibers to reduce the pressure drop. The stereocomposite polylactic acid fiber is combined with the beaded structure, and the ZIF-8 nanocrystals with high surface activity are tightly embedded in the surface of the stereocomposite polylactic acid fiber using a multi-needle electrospinning process. The obtained fiber filtration membrane has the advantages of high surface potential, high dielectric constant, high specific surface area, high antibacterial efficiency, ultra-low air resistance, high heat resistance, and high efficiency in intercepting ultrafine particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0039] Figure 1 A schematic diagram of a process flow for preparing a fiber filtration membrane according to Example 1 of the present invention is shown;
[0040] Figure 2 Shown is a scanning electron microscope image of a ZIF-8 crystal prepared according to Example 1 of the present invention;
[0041] Figure 3 A scanning electron microscope image of a ZIF-8 modified stereocomposite polylactic acid micro / nano multi-level fiber filtration membrane prepared according to Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0042] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0043] As analyzed in the background technology of this application, the prior art has the problem that the fiber filtration membrane has poor high temperature resistance and poor sterilization effect. In order to solve this problem, this application provides a ZIF-8 modified fiber filtration membrane and a preparation method thereof.
[0044] According to a typical embodiment of the present application, a method for preparing a ZIF-8 modified fiber filtration membrane is provided, the preparation method comprising: performing multi-needle electrospinning on a ZIF-8 dispersion, a first spinning solution and a second spinning solution to obtain a ZIF-8 modified fiber filtration membrane; wherein the mass ratios of poly-L-lactic acid and poly-D-lactic acid in the first spinning solution and the second spinning solution are independently 1:1 to 50:1, and the sum of the concentrations of poly-L-lactic acid and poly-D-lactic acid in the first spinning solution is 80 to 100 g / L; the sum of the concentrations of poly-L-lactic acid and poly-D-lactic acid in the second spinning solution is 60 to 80 g / L.
[0045] In the preparation method of the fiber filter membrane modified by ZIF-8, the blended solution of poly (dextral lactic acid) and poly (lextral lactic acid) is electrospun to form a stereocomposite polylactic acid fiber, wherein the stereocomposite crystals in the stereocomposite polylactic acid fiber can effectively increase the crystallinity of PLA and improve the heat resistance of PLA products. The preparation method constructs a beaded structure along the axis of the nanofiber to optimize the packing density of the nanofiber and adjust the distance between the nanofibers to reduce the pressure drop. The stereocomposite polylactic acid fiber is combined with the beaded structure, and the ZIF-8 nanocrystals with high surface activity are tightly embedded in the surface of the stereocomposite polylactic acid fiber using a multi-needle electrospinning process. The obtained fiber filter membrane has the advantages of high surface potential, high dielectric constant, high specific surface area, high antibacterial efficiency, ultra-low air resistance, high heat resistance, and high efficiency in intercepting ultrafine particles.
[0046] Multi-needle electrospinning is a technology for preparing fiber membranes. This technology uses the action of an electric field to inject different types of material solutions or melts into multiple injection pumps with fine-pore needle tips, and applies high voltage to form droplets of the material. The droplets are then stretched into fibers through the action of the electric field force. Finally, the prepared fibers are fixed on the collector to obtain a fiber membrane. The fiber membrane prepared by multi-needle electrospinning technology has the advantages of porous structure, controllable diameter, high specific surface area, good internal connectivity, uniform morphology, and excellent mechanical properties.
[0047] Metal-organic frameworks (MOFs) composed of metal ions and organic ligands are an emerging type of porous crystalline material with the characteristics of strong functionality, large porosity and specific surface area, adjustable pore size, and good biocompatibility. Among them, zeolitic imidazolate framework-8 (ZIF-8) is a typical MOFs material with excellent unique properties, such as high thermal stability, high chemical stability, and high adsorption. In addition, ZIF-8 itself has ultra-high photocatalytic bactericidal activity. It can effectively activate O2 to form O under the catalytic action of sunlight. 2-and H2O2, oxidizing and killing pathogenic bacteria in the air. The fiber filtration membrane prepared by the fiber filtration membrane has the advantages of high surface potential, high dielectric constant, high specific surface area, high antibacterial efficiency, ultra-low air resistance, high heat resistance and high efficiency in intercepting ultrafine particles, etc.
[0048] In some embodiments of the present application, the ZIF-8 dispersion includes ZIF-8 crystals, a dispersant and a first solvent. The ZIF-8 dispersion is obtained by uniformly mixing and dispersing the ZIF-8 crystals, the dispersant and the first solvent.
[0049] In some preferred embodiments, the ZIF-8 crystal is a rhombic dodecahedron structure, which has the characteristics of large porosity, large specific surface area, good biocompatibility, and a series of properties such as high adsorption and electrostatic capture. Further preferably, the particle size of the ZIF-8 crystal is 300-500nm, and the pore size is 0.2-0.34nm.
[0050] Preferably, the dispersant is at least one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide solution, and sodium hexadecylbenzenesulfonate; preferably, the mass ratio of ZIF-8 crystals to the dispersant is 5:1 to 20:1.
[0051] Preferably, the first solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, dichloromethane, chloroform, tetrahydrofuran, chloroform and ethanol; preferably, the mass ratio of ZIF-8 crystals to the first solvent is 1:1000 to 1:20.
[0052] The above ZIF-8 crystals can be purchased from commercial products or prepared by existing methods. In some typical embodiments of the present application, the preparation method of ZIF-8 crystals includes: mixing 2-methylimidazole aqueous solution, template agent and zinc salt solution, reacting under microwave conditions, extracting and drying to obtain ZIF-8 nanocrystals. Preferably, the template agent is at least one of ethanolamine, diethylamine, l-histidine, polyethylene glycol, sodium dodecyl sulfate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide. Preferably, the mass ratio of 2-methylimidazole to the template agent is 50:1 to 600:1. Preferably, the zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate. The concentration of the zinc salt solution is preferably 0.02 to 5 mol / L, and the molar ratio of 2-methylimidazole to the zinc salt is preferably 7:1 to 10:1. Preferably, the reaction temperature is 80 to 200°C, and the reaction time is 5 to 120 min; preferably, the output power of the microwave reaction device providing microwave conditions is 200 to 1500W.
[0053] When preparing the above-mentioned first spinning solution and the second spinning solution, a solvent can be selected in the prior art to dissolve poly-L-lactic acid and poly-D-lactic acid for preparation. In some embodiments of the present application, the solvents of the first spinning solution and the second spinning solution are independently selected from any one or more of dimethylformamide, ethyl acetate, acetone, dichloromethane, chloroform and ethanol. In some embodiments of the present application, in order to simplify the preparation method of the first spinning solution and the second spinning solution, poly-L-lactic acid and poly-D-lactic acid can be dissolved in solvents respectively, and then the solutions of the two can be mixed according to the ratio and concentration of poly-L-lactic acid and poly-D-lactic acid in the first spinning solution and the second spinning solution. If necessary, a solvent can be added to obtain a suitable concentration.
[0054] Specifically, the mass ratio of poly-L-lactic acid to poly-D-lactic acid in the first spinning solution and the second spinning solution can be 1:1, 2:1, 5:1, 8:1, 10:1, 12:1, 15:1, 17:1, 20:1, 23:1, 25:1, 27:1, 30:1, 33:1, 35:1, 40:1, 42:1, 45:1, 48:1, etc., but is not limited thereto. The mass ratio of poly-L-lactic acid to poly-D-lactic acid in the first spinning solution and the second spinning solution can be the same or different.
[0055] Specifically, the sum of the concentrations of poly-L-lactic acid and poly-D-lactic acid in the first spinning solution can be 80 g / L, 82 g / L, 84 g / L, 86 g / L, 88 g / L, 90 g / L, 92 g / L, 94 g / L, 95 g / L, 97 g / L, 99 g / L, etc., or other values within the above range.
[0056] Specifically, the sum of the concentrations of poly-L-lactic acid and poly-D-lactic acid in the second spinning solution can be 60 g / L, 62 g / L, 64 g / L, 66 g / L, 68 g / L, 70 g / L, 72 g / L, 74 g / L, 75 g / L, 77 g / L, 79 g / L, etc., and of course it can also be other values within the above range.
[0057] In some embodiments of the present application, in multi-needle electrospinning, the inner diameter of the spinning metal needle used in the first spinning solution is 0.60-0.86 mm, the positive voltage used is 10-20 kV, and the negative voltage is 1-5 kV; preferably, the consumption rate of the first spinning solution is 2-3 mL / h, the receiving distance is 10-30 cm, and the roller speed is 500-1500 rpm. Preferably, the diameter of the fiber obtained by the first spinning solution is 1-15 μm.
[0058] In some embodiments of the present application, in multi-needle electrospinning, the inner diameter of the spinning metal needle used in the second spinning solution is 0.33-0.50 mm, the positive voltage used is 15-30 kV, and the negative voltage is 1-15 kV; preferably, the consumption rate of the second spinning solution is 0.5-2 mL / h, the receiving distance is 10-30 cm, and the roller speed is 500-1500 rpm. Preferably, the diameter of the fiber obtained by the second spinning solution is 30-300 nm.
[0059] In some preferred embodiments of the present application, in multi-needle electrospinning, the inner diameter of the spinning metal needle used for the ZIF-8 dispersion is 0.33 to 0.86 mm, the positive voltage used is 5 to 30 kV, and the negative voltage is 1 to 15 kV; the consumption rate of the ZIF-8 dispersion is 0.1 to 2 mL / h, the receiving distance is 5 to 20 cm, and the roller speed is 100 to 1000 rpm.
[0060] In some preferred embodiments of the present application, the environment temperature of the multi-needle electrospinning is 20-30° C., and the relative humidity is 25-45%, and the performance of the prepared ZIF-8 modified fiber filtration membrane is better.
[0061] In some typical embodiments of the present application, the fiber filter membrane modified by ZIF-8 includes a beaded structure. The formation of the beaded structure is mainly due to the fact that when the mass fraction of the electrospinning solution is low, the entanglement force between the polymer molecular chains is small. Under the same electric field strength, the effect of the electric field force is relatively large, which easily causes the spinning jet to be discontinuous and produces a beaded structure. The beaded structure is mainly distributed on the nano-scale stereocomposite polylactic acid fiber obtained by the second spinning solution with a lower mass fraction of poly-L-lactic acid and poly-D-lactic acid. The existence of the beaded structure makes the fiber pores more evenly distributed, reducing the air resistance of the polylactic acid electrospinning membrane during high flow filtration. Secondly, by increasing the concentration of the first spinning solution, reducing the spinning voltage, reducing the roller speed, and increasing the propulsion speed of the solution, micron-scale stereocomposite polylactic acid fibers can be obtained, which mainly plays the role of filtering dust and intercepting large particles. The nano-scale stereocomposite polylactic acid fiber is combined with the beaded structure, and the filter membrane prepared has the performance of high efficiency and low resistance.
[0062] Preferably, the beaded structure has an elongated spindle shape with an average width of 500 to 1000 nm and an average length of 600 to 1500 nm.
[0063] In some embodiments of the present application, the thickness of the ZIF-8 modified fiber filtration membrane is 80-300 μm, specifically 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 220 μm, 240 μm, 260 μm, 280 μm, 290 μm, etc., and of course it can also be other values within the above range.
[0064] In some preferred embodiments of the present application, the surface potential of the fiber filter membrane modified by ZIF-8 is 7 to 15.5 kV. Preferably, the dielectric constant of the fiber filter membrane modified by ZIF-8 is 5 to 13 F / m. The size of the surface potential and the dielectric constant are closely related to the filtering performance of the filter membrane. The fiber filter membrane with the surface potential and the dielectric constant within the above range is convenient for obtaining better filtering performance.
[0065] In some embodiments of the present application, the specific surface area of the ZIF-8 modified fiber filtration membrane is 330.5 to 550.5 m 2 / g, the larger the specific surface area, the more particle attachment points it provides and the better the filtering performance of the material.
[0066] Preferably, under illumination conditions, the high-efficiency antibacterial inhibition rate of the ZIF-8 modified fiber filter membrane against Escherichia coli is greater than or equal to 97.6%, and the inhibition rate against Staphylococcus aureus is greater than or equal to 99.5%; preferably, at a gas flow rate of 10 to 85 L / min, the air resistance of the ZIF-8 modified fiber filter membrane is low ≤100 Pa.
[0067] The above-mentioned ZIF-8 modified fiber filtration membrane can efficiently intercept ultrafine particles. In some embodiments of the present application, PM 0.3 Filtration efficiency ≥ 91.0%, PM 0.3 The filtration efficiency is ≥99.6%.
[0068] In some embodiments of the present application, at 100°C, the ZIF-8 modified fiber filtration membrane has a significant effect on PM 0.3 The removal efficiency is greater than or equal to 90.5%; for PM 2.5 The removal efficiency is greater than or equal to 99.5%. The ZIF-8 modified fiber filtration membrane prepared by the above preparation method has high temperature resistance and also has good filtration performance at high temperature.
[0069] According to another typical embodiment of the present application, a ZIF-8 modified fiber filter membrane is provided, and the ZIF-8 modified fiber filter membrane is prepared by any one of the above methods for preparing a ZIF-8 modified fiber filter membrane. The fiber filter membrane has the advantages of high surface potential, high dielectric constant, high specific surface area, high antibacterial efficiency, ultra-low air resistance, high heat resistance, and high efficiency in intercepting ultrafine particles.
[0070] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.
[0071] Example 1
[0072] A ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0073] S11. Preparation of ZIF-8 nanocrystals: 2-methylimidazole was dissolved in deionized water, and the template agent ethanolamine (the mass ratio of 2-methylimidazole to ethanolamine was 50:1) was added, and the mixture was evenly mixed with the zinc salt (zinc acetate, 5 mol / L) solution (the molar ratio of 2-methylimidazole to zinc acetate was 7:1), and the mixture was placed in a microwave reactor (output power 1500 W, temperature 200°C, time 5 min) for microwave-assisted synthesis. After the reaction, a ZIF-8 dispersion was obtained, and the dispersion was centrifuged (i.e., extracted) and then dried (drying temperature was 60°C, time 48 h) to obtain ZIF-8 crystals (rhombic dodecahedron structure, crystal size was 500 nm, and pore size was 0.34 nm). The microstructure of ZIF-8 nanocrystals with rhombic dodecahedron morphology was observed by field emission scanning electron microscopy (model JSM-7900F, Japan Electronics), and its scanning electron microscope image is shown in FIG. Figure 2 As shown;
[0074] S12, preparing a stable ZIF-8 dispersion: dispersing ZIF-8 crystals in dimethylformamide solvent (the mass ratio of ZIF-8 to dimethylformamide is 1:20), adding dispersant polyvinyl pyrrolidone (the mass ratio of ZIF-8 to polyvinyl pyrrolidone is 5:1), and obtaining a stable ZIF-8 dispersion after magnetic stirring for 6 hours;
[0075] S13, preparing a spinning solution: dissolving poly-L-lactic acid (PLLA) and poly-D-lactic acid (PDLA) in a mass ratio of 1:1 in a solvent of dimethylformamide, respectively, to prepare a relatively high concentration spinning solution 1 (concentration of 100 g / L) and a relatively low concentration spinning solution 2 (concentration of 60 g / L);
[0076] S14. Preparation of ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane: The ZIF-8 stable dispersion (1 mL) was loaded into a syringe pump with a metal needle inner diameter of 0.33 mm (the positive voltage used was 30 kV, the negative voltage was 1 kV, the consumption rate was 2 mL / h, the receiving distance was 20 cm, and the roller speed was 1000 rpm), the spinning solution 1 was loaded into a syringe pump with a metal needle inner diameter of 0.86 mm (1 mL, the electrospinning positive voltage was 10 kV, the negative voltage was 5 kV, the receiving distance was 10 cm, the solution consumption rate was 3.5 mL / h, and the roller speed was 500 rpm), and the spinning solution 2 was loaded into a metal syringe pump with a metal needle inner diameter of 0.86 mm. In a syringe pump with a needle inner diameter of 0.33 mm (1 mL was taken, the positive voltage for electrospinning was 30 kV, the negative voltage was 1 kV, the receiving distance was 30 cm, the solution consumption rate was 0.5 mL / h, and the roller speed was 500 rpm), multi-needle electrospinning (ambient temperature was 20 ° C, relative humidity was 45%) was carried out to prepare ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane (the fiber diameter obtained from spinning solution 1 was 15 μm, the fiber diameter obtained from spinning solution 2 was 30 nm, the thickness of the obtained fiber membrane was 300 μm, the beaded morphology was spindle-shaped, the average width was 500 nm, and the average length was 600 nm). The scanning electron microscope image is shown as follows Figure 3 As shown. Figure 3 It can also be seen that a large number of ZIF-8 crystals are embedded in the surface of stereocomposite polylactic acid micro / nanomulti-level fibers. The large amount of embedding of these crystals can increase the specific surface area of the fibers and enhance the antibacterial and filtration properties of the fiber membrane.
[0077] Example 2
[0078] A ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane and a preparation method thereof, comprising the following steps:
[0079] S21, preparation of ZIF-8 nanocrystals: 2-methylimidazole was dissolved in deionized water, l-histidine was added (the mass ratio of 2-methylimidazole to l-histidine was 100:1), and the mixture was uniformly mixed with zinc chloride (1 mol / L) solution (the molar ratio of 2-methylimidazole to zinc chloride was 8:1), and the mixture was placed in a microwave reactor (output power 200 W, temperature 80° C., time 120 min), and ZIF-8 dispersion was obtained after reaction, and the dispersion was filtered and dried (drying temperature was 100° C., time 5 h) to obtain ZIF-8 nanocrystals (rhombic dodecahedron structure, crystal size was 450 nm, pore size was 0.30 nm);
[0080] S22, preparing a stable ZIF-8 dispersion: dispersing ZIF-8 crystals in chloroform (the mass ratio of ZIF-8 to chloroform is 1:50), adding sodium hexadecylbenzenesulfonate (the mass ratio of ZIF-8 to sodium hexadecylbenzenesulfonate is 10:1), and obtaining a stable ZIF-8 dispersion after ultrasonic dispersion for 3 hours;
[0081] S23, preparing an electrospinning solution: dissolving PLLA and PDLA in a mass ratio of 10:1 in dimethylformamide, respectively, to prepare a relatively high concentration spinning solution 1 (concentration of 100 g / L) and a relatively low concentration spinning solution 2 (concentration of 60 g / L);
[0082] S24. Preparation of ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane: The ZIF-8 stable dispersion (1 mL) was loaded into a syringe pump with a metal needle inner diameter of 0.33 mm (the positive voltage used was 20 kV, the negative voltage was 2 kV, the consumption rate was 1.5 mL / h, the receiving distance was 20 cm, and the roller speed was 500 rpm). The spinning solution 1 was loaded into a syringe pump with a metal needle inner diameter of 0.86 mm (1 mL, the electrospinning positive voltage was 13 kV, the negative voltage was 2 kV, the receiving distance was 15 cm, the solution consumption rate was 3 mL / h, and the roller speed was 700 rpm). Solution 2 was loaded into a syringe pump with a metal needle inner diameter of 0.33 mm (1 mL was taken, the positive voltage for electrospinning was 20 kV, the negative voltage was 5 kV, the receiving distance was 15 cm, the solution consumption rate was 1 mL / h, and the roller speed was 700 rpm), and multi-needle electrospinning was performed (ambient temperature was 22 ° C, relative humidity was 40%) to prepare ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane (the fiber diameter obtained from spinning solution 1 was 10 μm, the fiber diameter obtained from spinning solution 2 was 30 nm, the thickness of the obtained fiber membrane was 250 μm, the beaded morphology was spindle-shaped, the average width was 600 nm, and the average length was 800 nm).
[0083] Example 3
[0084] A ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane and a preparation method thereof, comprising the following steps:
[0085] S31, preparation of ZIF-8 nanocrystals: 2-methylimidazole was dissolved in deionized water, diethylamine was added (the mass ratio of 2-methylimidazole to diethylamine was 200:1), and the mixture was uniformly mixed with zinc sulfate (2 mol / L) solution (the molar ratio of 2-methylimidazole to zinc sulfate was 9:1), and the mixture was placed in a microwave reactor (output power 300 W, temperature 110° C., time 20 min), and ZIF-8 dispersion was obtained after reaction, and the dispersion was centrifuged and dried (drying temperature was 70° C., time 10 h) to obtain ZIF-8 nanocrystals (rhombic dodecahedron structure, crystal size was 400 nm, pore size was 0.27 nm);
[0086] S32, preparing a stable ZIF-8 dispersion: dispersing ZIF-8 crystals in dimethylformamide (the mass ratio of ZIF-8 to dimethylformamide is 1:100), adding polyvinyl pyrrolidone (the mass ratio of ZIF-8 to polyvinyl pyrrolidone is 15:1), and obtaining a stable ZIF-8 dispersion after magnetic stirring for 6 hours;
[0087] S33, preparing an electrospinning solution: dissolving PLLA and PDLA in a mass ratio of 20:1 in a mixed solvent of dimethylformamide and dichloromethane (the volume ratio of DMF to DCM is 7:3) to prepare a relatively high concentration spinning solution 1 (concentration of 90 g / L) and a relatively low concentration spinning solution 2 (concentration of 70 g / L);
[0088] S34. Preparation of ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane: The ZIF-8 stable dispersion (1 mL) was loaded into a syringe pump with a metal needle inner diameter of 0.33 mm (the positive voltage used was 10 kV, the negative voltage was 10 kV, the consumption rate was 1 mL / h, the receiving distance was 15 cm, and the roller speed was 500 rpm), the spinning solution 1 was loaded into a syringe pump with a metal needle inner diameter of 0.67 mm (1 mL, the electrospinning positive voltage was 15 kV, the negative voltage was 3 kV, the receiving distance was 20 cm, the solution consumption rate was 2.5 mL / h, and the roller speed was 1000 rpm), and the spinning solution 2 Load it into a syringe pump with a metal needle inner diameter of 0.40 mm (take 1 mL, the positive voltage for electrospinning is 25 kV, the negative voltage is 10 kV, the receiving distance is 20 cm, the solution consumption rate is 1.5 mL / h, and the roller speed is 1000 rpm), and carry out multi-needle electrospinning (ambient temperature is 25 ° C, relative humidity is 35%) to prepare ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane (the fiber diameter obtained from spinning solution 1 is 7 μm, the fiber diameter obtained from spinning solution 2 is 100 nm, the thickness of the obtained fiber membrane is 200 μm, the beaded morphology is spindle-shaped, the average width is 800 nm, and the average length is 1000 nm).
[0089] Example 4
[0090] A ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane and a preparation method thereof, comprising the following steps:
[0091] S41. Preparation of ZIF-8 nanocrystals: Dissolve 2-methylimidazole in deionized water, add polyethylene glycol (the mass ratio of 2-methylimidazole to polyethylene glycol is 600:1), mix evenly with zinc nitrate (0.02 mol / L) solution (the molar ratio of 2-methylimidazole to zinc nitrate is 10:1), place in a microwave reactor (output power 400 W, temperature 115°C, time 15 min), obtain ZIF-8 dispersion after reaction, filter the dispersion and dry it (drying temperature is 80°C, time 8 h) to obtain ZIF-8 nanocrystals (rhombic dodecahedron structure, crystal size is 300 nm, pore size is 0.20 nm).
[0092] S42, preparing a stable ZIF-8 dispersion: dispersing ZIF-8 crystals in ethyl acetate (the mass ratio of ZIF-8 to ethyl acetate is 1:1000), adding sodium hexadecylbenzenesulfonate (the mass ratio of ZIF-8 to sodium hexadecylbenzenesulfonate is 20:1), and obtaining a stable ZIF-8 dispersion after ultrasonic dispersion for 6 hours;
[0093] S43, preparing a spinning solution: dissolving PLLA and PDLA in a mass ratio of 50:1 in ethyl acetate respectively to prepare a relatively high concentration spinning solution 1 (concentration of 80 g / L) and a relatively low concentration spinning solution 2 (concentration of 80 g / L);
[0094] S44. Preparation of ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane: The ZIF-8 stable dispersion (0.5 mL) was loaded into a syringe pump with a metal needle inner diameter of 0.67 mm (the positive voltage used was 10 kV, the negative voltage was 1 kV, the consumption rate was 0.1 mL / h, the receiving distance was 5 cm, and the roller speed was 100 rpm), and the spinning solution 1 was loaded into a syringe pump with a metal needle inner diameter of 0.60 mm (0.8 mL, the electrospinning positive voltage was 20 kV, the negative voltage was 1 kV, the receiving distance was 15 cm, the solution consumption rate was 2 mL / h, and the roller speed was 1500 rpm), and the spinning solution 2 was loaded into a syringe pump with a metal needle inner diameter of 0.50 mm (0.8 mL was taken, the positive voltage for electrospinning was 15 kV, the negative voltage was 15 kV, the receiving distance was 25 cm, the solution consumption rate was 0.5 mL / h, and the roller speed was 1500 rpm), and multi-needle electrospinning was performed (ambient temperature was 30 ° C, relative humidity was 25%) to prepare ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane (the fiber diameter obtained from spinning solution 1 was 1 μm, the fiber diameter obtained from spinning solution 2 was 200 nm, the thickness of the obtained fiber membrane was 80 μm, the beaded morphology was spherical, the average width was 1000 nm, and the average length was 1500 nm).
[0095] Comparative Example 1
[0096] This comparative example uses the same method as Example 1 to prepare a filtration membrane, except that in this example, PDLA is not added to PLLA, but ZIF-8 nanocrystals are directly embedded in pure PLLA fibers by electrospinning. The specific method is as follows:
[0097] 2-Methylimidazole was dissolved in deionized water, ethanolamine was added (the mass ratio of 2-methylimidazole to ethanolamine was 50:1), and the mixture was evenly mixed with zinc acetate (5 mol / L) solution (the molar ratio of 2-methylimidazole to zinc acetate was 7:1), and the mixture was placed in a microwave reactor (output power 1500 W, temperature 200°C, time 5 min), and ZIF-8 dispersion was obtained after reaction. The dispersion was centrifuged and then dried (drying temperature was 60°C, time 48 h) to obtain ZIF-8 nanocrystals (rhombic dodecahedron structure, crystal size was 500 nm, pore size was 0.34 nm).
[0098] The ZIF-8 crystals were dispersed in dimethylformamide (the mass ratio of ZIF-8 to dimethylformamide was 1:20), polyvinyl pyrrolidone was added (the mass ratio of ZIF-8 to polyvinyl pyrrolidone was 5:1), and a stable ZIF-8 dispersion was obtained after magnetic stirring for 6 h.
[0099] PLLA was dissolved in dimethylformamide to prepare a relatively high concentration spinning solution 1 (with a concentration of 100 g / L) and a relatively low concentration spinning solution 2 (with a concentration of 60 g / L).
[0100] The ZIF-8 stable dispersion (1 mL) was loaded into a syringe pump with a metal needle inner diameter of 0.33 mm (the positive voltage used was 30 kV, the negative voltage was 1 kV, the consumption rate was 2 mL / h, the receiving distance was 20 cm, and the roller speed was 1000 rpm). The spinning solution 1 was loaded into a syringe pump with a metal needle inner diameter of 0.86 mm (1 mL, the electrospinning positive voltage was 10 kV, the negative voltage was 5 kV, the receiving distance was 10 cm, the solution consumption rate was 3 mL / h, and the roller speed was 500 rpm). The spinning solution 2 was loaded into a syringe pump with a metal needle inner diameter of 0.33 mm. m injection pump (take 1mL, electrospinning positive voltage is 30kV, negative voltage is 1kV, receiving distance is 30cm, solution consumption rate is 0.5mL / h, roller speed is 500rpm), multi-needle electrospinning (ambient temperature is 20℃, relative humidity is 45%) is carried out to prepare ZIF-8 modified polylactic acid micro / nano multi-grade fiber filtration membrane (the fiber diameter obtained from spinning solution 1 is 15μm, the fiber diameter obtained from spinning solution 2 is 30nm, the thickness of the obtained fiber membrane is 300μm, the beaded morphology is spindle-shaped, the average width is 500nm, and the average length is 600nm).
[0101] Comparative Example 2
[0102] The method of Example 2 was used to prepare a ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane. The difference is that in this example, the ZIF-8 nanocrystals were not embedded into the surface of the polylactic acid fiber by multi-needle electrospinning, but the ZIF-8 stable dispersion was directly filtered on the polylactic acid micro / nano multi-stage fiber filtration membrane after electrospinning by mechanical method. The specific method is as follows:
[0103] 2-Methylimidazole was dissolved in deionized water, l-histidine was added (the mass ratio of 2-methylimidazole to l-histidine was 100:1), and the mixture was evenly mixed with zinc chloride (1 mol / L) solution (the molar ratio of 2-methylimidazole to zinc chloride was 8:1), and the mixture was placed in a microwave reactor (output power 200 W, temperature 80°C, time 120 min), and ZIF-8 dispersion was obtained after reaction. The dispersion was filtered and dried (drying temperature was 100°C, time 5 h) to obtain ZIF-8 nanocrystals (rhombic dodecahedron structure, crystal size was 450 nm, pore size was 0.30 nm).
[0104] The ZIF-8 crystals were dispersed in chloroform (the mass ratio of ZIF-8 to chloroform was 1:50), sodium hexadecylbenzenesulfonate was added (the mass ratio of ZIF-8 to sodium hexadecylbenzenesulfonate was 10:1), and a stable ZIF-8 dispersion was obtained after ultrasonic dispersion for 3 hours.
[0105] PLLA and PDLA with a mass ratio of 10:1 were dissolved in dimethylformamide to prepare relatively high concentration spinning solution 1 (concentration of 100 g / L) and relatively low concentration spinning solution 2 (concentration of 60 g / L). The spinning solution 1 was loaded into a syringe pump with a metal needle inner diameter of 0.86 mm (1 mL, electrospinning positive voltage of 13 kV, negative voltage of 2 kV, receiving distance of 15 cm, solution consumption rate of 3 mL / h, roller speed of 700 rpm), and the spinning solution 2 was loaded into a syringe pump with a metal needle inner diameter of 0.33 mm (1 mL, electrospinning positive voltage of 20 kV, negative voltage of 5 kV, receiving distance of 15 cm, solution consumption rate of 1 mL / h, roller speed of 700 rpm), and multi-needle electrospinning (ambient temperature of 22 ° C, relative humidity of 40%) was performed to prepare a stereocomposite polylactic acid micro / nano multi-level fiber filtration membrane. 1 mL of ZIF-8 stable dispersion was directly filtered onto a stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane. After drying, a ZIF-8 modified stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane was obtained (the fiber diameter obtained from spinning solution 1 was 10 μm, the fiber diameter obtained from spinning solution 2 was 30 nm, the thickness of the obtained fiber membrane was 250 μm, the beaded morphology was spindle-shaped, the average width was 600 nm, and the average length was 800 nm).
[0106] Comparative Example 3
[0107] PLLA and PDLA with a mass ratio of 20:1 were dissolved in a mixed solvent of dimethylformamide and dichloromethane (the volume ratio of DMF to DCM was 7:3) to prepare a relatively high concentration spinning solution 1 (concentration of 90 g / L) and a relatively low concentration spinning solution 2 (concentration of 70 g / L).
[0108] The spinning solution 1 was loaded into a syringe pump with a metal needle inner diameter of 0.67 mm (1 mL was taken, the positive voltage for electrospinning was 15 kV, the negative voltage was 3 kV, the receiving distance was 20 cm, the solution consumption rate was 2.5 mL / h, and the roller speed was 1000 rpm), and the spinning solution 2 was loaded into a syringe pump with a metal needle inner diameter of 0.40 mm (1 mL was taken, the positive voltage for electrospinning was 25 kV, the negative voltage was 10 kV, the receiving distance was 20 cm, the solution consumption rate was 1.5 mL / h, and the roller speed was 1000 rpm), and multi-needle electrospinning was performed (ambient temperature was 25°C, relative humidity was 35%) to prepare a stereocomposite polylactic acid micro / nano multi-stage fiber filtration membrane (the fiber diameter obtained from spinning solution 1 was 7 μm, the fiber diameter obtained from spinning solution 2 was 100 nm, the thickness of the obtained fiber membrane was 200 μm, the beaded morphology was spindle-shaped, the average width was 800 nm, and the average length was 1000 nm).
[0109] Comparative Example 4
[0110] The only difference from Example 1 is that in S13, PLLA and PDLA with a mass ratio of 1:1 are dissolved in dimethylformamide to prepare a relatively high concentration spinning solution 1 (concentration of 120 g / L) and a relatively low concentration spinning solution 2 (concentration of 60 g / L);
[0111] The fiber filtration membranes prepared in the above examples and comparative examples were subjected to performance tests in the following manner. The test results are listed in Tables 1 and 2.
[0112] Scanning electron microscopy observation : The microstructure of ZIF-8 crystals and finished fiber filtration membranes was observed by field emission scanning electron microscopy (model JSM-7900F, JEOL).
[0113] Specific surface area test The nitrogen adsorption isotherms were measured at 77 K using a gas adsorption instrument (ASAP 2060, Micromeritics, USA).
[0114] Surface potential test The surface potential of the nanofiber membrane was tested using a non-contact electrostatic meter (VM54XQS, Quatek, USA). The test height was 2 cm, the temperature and humidity were constant at 25°C and 45%, and 20 data points were randomly collected for each sample and the average value was taken.
[0115] Dielectric constant test : The dielectric constant was tested using a dielectric constant tester (model Wayne Kerr 6500B, Wayne Kerr, UK).
[0116] Respiratory resistance test: A micromanometer (AIRPRO AP800, TSI, USA), an anthropomorphic respirator and a simulated human head were used to measure the respiratory resistance. The gas flow rate was set to 85L / min, and the filter membrane was encapsulated on the simulated human head. The air pressure in the cavity composed of the filter material and the human head and the atmospheric pressure were measured and the difference was made. The experiment was repeated three times and the average value was taken to calculate the respiratory resistance of the filter membrane.
[0117] Filtration performance test :The fiber membrane (area 113.04cm 2 ) air filtration performance, the gas flow rate was set to 85L / min, and the particle size range of NaCl atomized particles produced by the aerosol generator was 0.1-10μm. At least 3 different positions of each group of fiber membranes were tested, and the results were averaged. The test results are shown in Table 1.
[0118] High heat resistance test :The filter membrane was placed in a W300 high temperature oven with a heating rate of 10℃ / min and connected to a filtration performance test system. A PM particle counter was used to measure the particle number concentration. Incense was used to generate particles. During the test, the particle concentration of each particle size remained relatively stable. The filter membrane was exposed to a high temperature of 100℃ for 2h and then its filtration performance was measured. The test results are shown in Table 2.
[0119] Antibacterial performance test :The selected bacteria were Escherichia coli and Staphylococcus aureus, and the strains were cultured in lysate broth (LB) medium at 37°C for 16 h. After incubation, 0.5 mL of Escherichia coli and 0.5 mL of Staphylococcus aureus were washed, combined, and suspended in 0.85% NaCl solution to obtain 1 mL of cell mixture with a cell density of 109 CFU / mL. Then the above NaCl solution was diluted 10 times to a cell density of 108 CFU / mL. A fiber membrane with a diameter of 10 cm was immersed in 100 μL of bacterial suspension. The fiber membrane was treated with light irradiation using a solar simulator (HSX-F300, NbeT, China). The optical density was measured using a solar power meter (VLP-2000, NBeT). The sample was kept at 25 cm from the light and irradiated for 30 minutes. The temperature was detected using a thermal imaging camera (HT-18, HTI, Dongguan, China). After illumination, the bacterial suspension was serially diluted and CFU counted until the cell density was about 102 CFU / mL. The plates were cultured overnight (37°C, RH75%), and the antibacterial efficiency was calculated by counting CFU.
[0120] Table 1
[0121]
[0122] Table 2
[0123]
[0124] Table 1 compares the surface potential, specific surface area, dielectric constant, filtration resistance, filtration performance and antibacterial performance test results of the obtained filtration membrane. It can be clearly seen from Table 1 that the filtration membrane prepared by combining stereocomposite polylactic acid micro / nano multi-grade fibers with ZIF-8 crystals has a high specific surface area (330.5-550.5 m 2 / g), high surface potential (7-15.5 kV) and high dielectric constant (5-13 F / m). The larger the specific surface area, the more particle attachment points it provides, and the better the filtration performance of the material. The size of the surface potential and the dielectric constant are closely related to the filtration performance of the filtration membrane. Examples 1-4 with higher surface potential have excellent filtration performance (PM 0.3 ≥91.0%,PM 2.5 ≥99.6%), and the pressure drop is extremely low (≤100Pa), and the prepared filter membrane has high efficiency and low resistance. In addition, the filter membrane also has excellent antibacterial properties. Under light conditions, the antibacterial rate of Escherichia coli can reach 98.7%, and the antibacterial rate of Staphylococcus aureus can reach 99.9%, which proves that it has good photocatalytic antibacterial properties, which is mainly due to the imidazole antibacterial organic ligands of ZIF-8 itself and Zn 2+ The presence of ZIF-8 can effectively activate O2 to form O under the catalytic effect of sunlight. 2- and H2O2, oxidizing and killing pathogenic bacteria in the air. Therefore, embedding ZIF-8 into the surface of stereocomposite polylactic acid fiber through electrospinning technology can make the prepared filter membrane have efficient photocatalytic antibacterial properties.
[0125] It is also meaningful that Table 2 compares the high heat resistance test results of the filter membranes obtained in the examples and the comparative examples. It can be clearly seen from the table that after the ZIF-8 crystals are embedded on the surface of the stereocomposite polylactic acid fiber, even after the filter membrane is placed at a high temperature of 100°C for 2h, Examples 1 to 4 still have a high filtration efficiency (PM at 100°C). 0.3 and PM 2.5 The removal efficiency of the filter membrane reached 90.5% and 99.5%, which proved that the filter membrane has high heat resistance. This is mainly due to the good high thermal stability of the ZIF-8 crystal itself, and the stereocomposite crystals in the stereocomposite polylactic acid fiber can effectively increase the crystallinity of PLA and improve the heat resistance of PLA products.
[0126] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: the technical solution proposed in this patent can make the prepared filter membrane have the advantages of high surface potential, high dielectric constant, high specific surface area, high antibacterial efficiency, ultra-low air resistance, high heat resistance and high efficiency in intercepting ultrafine particles, which are likely to benefit from (1) combining microwave-assisted synthesis with template method to optimize the preparation conditions of ZIF-8, so that the prepared ZIF-8 has high porosity, high surface activity and high structural integrity; (2) ZIF-8 crystals are tightly embedded in the surface of stereocomposite polylactic acid fiber, which can give full play to the electrostatic adsorption performance and antibacterial performance of ZIF-8. In addition, due to the synergistic effect of stereocomposite polylactic acid fiber and ZIF-8 material, the prepared filter membrane has high thermal stability; (3) constructing a beaded structure along the axis of nanofibers optimizes the packing density of nanofibers, improves the air filtration resistance of the filter membrane, and makes the prepared filter membrane have high efficiency and low resistance.
[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a ZIF-8 modified fiber filtration membrane, characterized in that: include: The ZIF-8 dispersion, the first spinning solution and the second spinning solution are subjected to multi-needle electrospinning to obtain the ZIF-8 modified fiber filtration membrane; Among them, the mass ratios of poly-L-lactic acid and poly-D-lactic acid in the first spinning solution and the second spinning solution are independently 1:1 to 50:1, the sum of the concentrations of poly-L-lactic acid and poly-D-lactic acid in the first spinning solution is 80 to 100 g / L; the sum of the concentrations of poly-L-lactic acid and poly-D-lactic acid in the second spinning solution is 60 to 80 g / L.
2. The method for preparing a ZIF-8 modified fiber filtration membrane according to claim 1, characterized in that: The ZIF-8 dispersion comprises ZIF-8 crystals, a dispersant and a first solvent; The ZIF-8 crystal has a rhombic dodecahedral structure. Preferably, the particle size of the ZIF-8 crystal is 300 to 500 nm, and the pore size is 0.2 to 0.34 nm; The dispersant is at least one of polyvinyl pyrrolidone, hexadecyl trimethyl ammonium bromide solution, and sodium hexadecyl benzene sulfonate; The first solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, dichloromethane, chloroform, and ethanol; Preferably, the mass ratio of the ZIF-8 crystals to the first solvent is 1:1000 to 1:20, and the mass ratio of the ZIF-8 crystals to the dispersant is 5:1 to 20:
1.
3. The method for preparing the ZIF-8 modified fiber filtration membrane according to claim 2, characterized in that: The preparation method of the ZIF-8 crystal comprises: mixing a 2-methylimidazole aqueous solution, a template agent and a zinc salt solution, reacting under microwave conditions, extracting and drying to obtain ZIF-8 nanocrystals; The template agent is at least one of ethanolamine, diethylamine, l-histidine, polyethylene glycol, sodium dodecyl sulfate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide, and the mass ratio of the 2-methylimidazole to the template agent is 50:1 to 600:1; The zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate, the concentration of the zinc salt solution is 0.02 to 5 mol / L, and the molar ratio of the 2-methylimidazole to the zinc salt is 7:1 to 10:1; Preferably, the reaction temperature is 80-200°C and the reaction time is 5-120 min; Preferably, the output power of the microwave reaction device providing the microwave conditions is 200-1500W.
4. The method for preparing a ZIF-8 modified fiber filtration membrane according to claim 1, characterized in that: The solvents of the first spinning solution and the second spinning solution are independently selected from any one or more of dimethylformamide, ethyl acetate, acetone, dichloromethane, chloroform, tetrahydrofuran, chloroform and ethanol.
5. The method for preparing the ZIF-8 modified fiber filtration membrane according to claim 1, characterized in that: In the multi-needle electrospinning, the inner diameter of the spinning metal needle used in the first spinning solution is 0.60-0.86 mm, the positive voltage used is 10-20 kV, and the negative voltage is 1-5 kV; The consumption rate of the first spinning solution is 2-3 mL / h, the receiving distance is 10-30 cm, and the roller speed is 500-1500 rpm.
6. The method for preparing a ZIF-8 modified fiber filtration membrane according to claim 1, characterized in that: In the multi-needle electrospinning, the inner diameter of the spinning metal needle used in the second spinning solution is 0.33-0.50 mm, the positive voltage used is 15-30 kV, and the negative voltage is 1-15 kV; The consumption rate of the second spinning solution is 0.5-2 mL / h, the receiving distance is 10-30 cm, and the roller speed is 500-1500 rpm.
7. The method for preparing a ZIF-8 modified fiber filtration membrane according to claim 1, characterized in that: In the multi-needle electrospinning, the inner diameter of the spinning metal needle used for the ZIF-8 dispersion is 0.33-0.86 mm, the positive voltage used is 5-30 kV, and the negative voltage is 1-15 kV; The consumption rate of the ZIF-8 dispersion is 0.1-2 mL / h, the receiving distance is 5-20 cm, and the roller speed is 100-1000 rpm.
8. The method for preparing a ZIF-8 modified fiber filtration membrane according to claim 1, characterized in that: The environment temperature of the multi-needle electrospinning is 20-30°C and the relative humidity is 25-45%; The diameter of the fiber obtained by the first spinning solution is 1 to 15 μm; The diameter of the fiber obtained by the second spinning solution is 30 to 300 nm.
9. The method for preparing a ZIF-8 modified fiber filtration membrane according to any one of claims 1 to 8, characterized in that: The ZIF-8 modified fiber filtration membrane comprises a beaded structure, the beaded structure has an elongated spindle shape, an average width of 500 to 1000 nm, and an average length of 600 to 1500 nm; The thickness of the ZIF-8 modified fiber filtration membrane is 80 to 300 μm; The surface potential of the ZIF-8 modified fiber filtration membrane is 7 to 15.5 kV; The dielectric constant of the ZIF-8 modified fiber filtration membrane is 5 to 13 F / m; The specific surface area of the ZIF-8 modified fiber filtration membrane is 330.5 to 550.5 m 2 / g; Under light conditions, the ZIF-8 modified fiber filter membrane has a high-efficiency antibacterial rate of 97.6% or more against Escherichia coli and 99.5% or more against Staphylococcus aureus; At a gas flow rate of 10 to 85 L / min, the air resistance of the ZIF-8 modified fiber filtration membrane is low, ≤ 100 Pa; At 100 °C, the ZIF-8 modified fiber filtration membrane had a significant effect on PM 0.3 The removal efficiency is greater than or equal to 90.5%; for PM 2.5 The removal efficiency is greater than or equal to 99.5%.
10. A ZIF-8 modified fiber filtration membrane, characterized in that: The membrane is prepared by the method for preparing a ZIF-8 modified fiber filtration membrane according to any one of claims 1 to 9.
